Risk Factors Social-Emotional Development Disorders in Children - Nur Mutiara Fadhilah Hidayatullah BW; Rosdianah Rahim; Trisnawaty Trisnawaty (State Islamic University of Sunan Ampel, 2023)
Monitoring development in early childhood is one of the efforts that must be done from the womb until the child is five years old. Early childhood development includes 5 different aspects, namely physical, social, emotional, cognitive, and languange development. Social emotional development includes children's ability to build interactions between individuals and individuals with the environment. The Covid-19 pandemic is a factor that can pose a risk to early childhood mental and behavioral health. This study's main goal was to look at the Covid-19 pandemic's potential risk factors for children's social-emotional development issues. The research method used an observational analytic design. Sampling through purposive sampling technique with a total 89 samples. This study using primary data from interviews with ASQ: SE, PSDQ, and respondent data sheet. The results of the study obtained mother’s education, socioeconomic status, parenting pattern, and exclusive breastfeeding as risk factors associated with impaired early childhood social emotional development during the Covid-19 pandemic. The results of statistical analysis through the Pearson Chi-Square test was obtained p-value <0,05.